Modeling simulation on amplifying magnetic fields in supernova remnants with an intense laser - Wei Sun; Zhu Lei; Chong Lv; Jiayong Zhong; Mengqi Jin; Jianzhao Wang; Baoxian Tian; Zhao Wang (New Journal of Physics, 2023)
Local magnetic field enhancement in supernova remnants (SNRs) is a natural laboratory for studying the amplification effect of turbulent magnetic fields. In recent years, high-power laser devices have gradually matured as a tool for astronomical research that perfects observations and theoretical models. In this study, a model of the amplification effect of the turbulent magnetic field in SNRs by an intense laser is simulated using the radiation magnetohydrodynamic simulation program. We investigate and compare the evolutionary processes of unstable turbulence under different initial disturbance modes, directions, and intensities of external magnetic fields and obtain the magnetic energy spectrum and magnetic field magnification. The results demonstrate that the fluid motion associated with Rayleigh–Taylor instability will stretch the environmental magnetic field significantly, with an intensity amplified by two orders of magnitude. The environmental magnetic field perpendicular to the laser injection direction is decisive during magnetic field amplification which is necessary to clarify the physical mechanism of magnetic field amplification in SNRs. Furthermore, it will deepen the understanding of the interstellar magnetic field’s evolution. The results also establish a reference for laser-driven magnetized plasma experiments in a robust magnetic environment.